ANALISIS EFEKTIVITAS BIAYA KOMBINASI OBAT ANTIHIPERTENSI PADA PASIEN RAWAT INAP DI RSUD Dr. SOEKARDJO TASIKMALAYA - Zulfah, Murniati (P3M STIKes Bakti Tunas Husada, 2019)
Hypertension is still being a health problem in the world. The blood pressure of most patients with hypertension are not controlled with single therapy meanwhile the medical costs are increasing annually, so that it needs to analyzed the cost effectiveness treatment to find out the most cost effective and provide the best outcome of therapy. This research aim to know the most effective antihypertensive two combination therapy in hospitalization RSUD dr. Soekardjo Tasikmalaya on 2017. This is a descriptive research that using pharmacoeconomic consideration with Cost Effectiveness Analysis method based on hospital perspective. This research using retrospective data of hypertension patient in hospitalization RSUD dr. Soekardjo Tasikmalaya during 2017 and sample who met the inclusion criteria were 35 patients. The data of study are categorized by kind of therapy and analyzed to get cost effective therapy for any category. The result showed that antihypertensive combinations are combination two, three and also four drugs. Cost effective treatment for any category are ACE-I-Diuretic for combination two drugs antihypertensive, ACE-I-β-Blocker-CCB for combination three drugs antihypertensive and ACE-Ia-ACE-Ib-CCB-Diuretic for combination three drugs antihypertensive. The lowest ICER Rp. 12.511,02 is shown between therapy combination ACE-I-CCB-Diuretic and ACE-I-ARB-Diuretic. Keywords: Cost Effectiveness Analysis, combination antihypertensive, hospitalization.